ARS AEVI 1994 - 1997 : Museum of Contemporary Art Sarajevo : The Passing. - Badovinac, Zdenka; Begic, Azra; Bertola, Chiara; Comi, Enrico R.; Corà, Bruno; Hadziomerspahic, Enver; Haracic, Midhat; Karamehmedovic, Muhamed; ARS AEVI, Sarajevo, 1994-1997 (Sarajevo : ARS AEVI, 1998)
Abramovic, Marina ; Accardi, Carla ; Asse, Evgeny ; Balka, Miroslaw ; Balkenhol, Stephan ; Bassiri, Bizhan ; Boetti, Alighiero ; Boltanski, Christian ; Brus, Günter ; Buren, Daniel ; Calle, Sophie ; Castellani, Enrico ; Dakic, Danica ; Deacon, Richard ; Dibbets, Jan ; Fishkin, Vadim ; Goldin, Nan ; Gutoff, Dimitri ; Inspection "Medical Hermeneutics" ; IRWIN ; Kabakov, Ilya ; Kapoor, Anish ; Kosuth, Joseph ; Kounellis, Jannis ; LeWitt, Sol ; Matthiacci, Eliseo ; Misiano, Viktor ; Nagasawa, Hidetoshi ; Numankadic, Edin ; Opalka, Roman ; Opie, Julian ; Paladino, Mimmo ; Panamarenko ; Pasic, Nusret ; Pistoletto, Michelangelo ; Plensa, Jaume ; Potrc, Marjetica ; Salvadori, Remo ; Schütte, Thomas ; Serrano, Andres ; Sherman, Cindy ; Skopljak, Mustafa ; Trockel, Rosemarie ; V.S.S.D. ; Viola, Bill ; West, Franz
biografie
Bosnisch & Engels & Italiaans
ARS AEVI - International Cultural Project, Museum of Contemporary Art, Sarajevo, 1998
boek